Portrait of the Utilization of ICT-Based Learning Media in Outlying Areas: Identification of Kindergarten Teachers - Marzuqoh, Nur Laili; Mayangsari, Dewi; Fitroh, Siti Fadjryana; Adhani, Dwi Nurhayati; Yuniar, Dias Putri; Latif, Muhammad Abdul; Fitriyono, Angga (Jurnal Pendidikan Anak, 2025)
The utilisation of Information and Communication Technology (ICT) in early childhood education is crucial for enhancing the quality of learning that is both interactive and engaging. This study aims to analyse the level of ICT-based learning media utilisation among kindergarten teachers in Bangkalan and identify the factors that support and hinder it. A quantitative descriptive method was employed using an online questionnaire that had been tested for validity and reliability (α = 0.89). The study involved 305 kindergarten teachers as respondents. Data were analysed using descriptive statistics through percentages and categorisation of utilisation levels. The results show that 96.7% of teachers have used ICT, with mobile phones being the most dominant medium (78%), indicating overutilisation. The main supporting factors are teacher motivation and school support, while obstacles include limited funding, network issues, and low teacher confidence. The findings imply the need for training and infrastructural support to enhance teachers' digital competence.